Design and Simulation of PFC Converter for Brushless SRM Drive - M. Rama Subbamma; V. Madhusudhan; K.S.R Anjaneyulu (Institute of Advanced Engineering and Science, 2016)
In most of the industrial applications, Switched Reluctance Motor (SRM) is mainly employed due to the reasons like having low maintenance and high efficiency. SRM consists of windings only on its stator, but would not have any windings on rotor thus having very simple construction. The available supply is AC. But AC cannot be directly supplied to SRM when used for air-conditioner application which is employed in this paper. Also power factor in the system needs to be corrected when using a SRM drive. Thus AC supply is fed to power factor correction (PFC) converter which is Buck-Boost converter here in this paper. The output of the PFC converter is fed to SRM through a simple asymmetrical converter. This PFC circuit consists of a simple diode bridge rectifier with Buck-Boost DC-DC converter. A suitable control circuit was proposed to control the input power factor under various loading conditions. This paper gives analysis of SRM drive for air-conditioner application with Buck-Boost converter based PFC circuit. A Matlab/simulink based model is developed and simulation results are presented. Simulation is carried out for different speed response.